DARK WEB – NEW TRANSNATIONAL SECURITY THREAT (Annual of the Faculty of Philosophy in Skopje, 2020)
In latest years, the Dark web has converted to one of the most debated themes incyber security circles. Recent academic analyses and media articles tend to focus howthe anonymous nature of the Darknet is used to enable criminal activities. This articleanalyses and underlines the major roles played by the Dark Web as a market; as acommunication platform; as an enabler of cybercrime; as an enabler of anonymous financialtransactions and as a proxy to a surface web. Precisely, it draw attention to the‘black market’ of the Internet–the dark web that represents such a hidden space, beingthe largest deployed anonymity network. This success is supported by numerous featuresthat are imbedded in the high-tech structure of the Dark web, for instance, secrecy,anonymity and the usage of cryptocurrencies. The distinctive environment ofDark Net markets as extremely anonymous and secretive, as well as reliable, makesthem an ultimate test case for the unrestrained online marketplace.
Keywords: DARK WEB; CYBER SECURITY; SECURITY THREAT; ILLEGAL ACTIVITIES; ILLEGAL SERVICES